Automatic Construction of 3D Building Property Rights Model Based on Visual Programing Language in China - Guocheng Qin; Yuqing Hu; Ling Wang; Ke Liu; Yimei Hou (Advances in Civil Engineering)
The accelerated development of society and the rapid advancement of urbanization are among the reasons for the current shortage of land resources. In China, the pressure of land resource shortage, the increasing height and complexity of buildings in cities, and the inadequate spatial expression ability of two-dimensional (2D) real estate data pose challenges to government departments that use 2D real estate data as basic management elements. Currently, an effective solution is to establish a three-dimensional (3D) building property rights model. However, this approach has low modeling efficiency, and the model cannot be divided into floor and house, cannot be linked to property rights information, and has a large size and high input cost. To address these problems, this paper presents an automatic method of constructing a 3D building property model based on visual programming language (VPL). The compatibility of this method with several different building types is tested, and the differences in cost, efficiency, and model size between this method and other modeling methods are compared and analyzed. Results show that the average modeling time has been reduced to less than 2 min, representing an efficiency improvement of over 80%. Furthermore, the model size has been reduced by more than 90%. This method cannot only stereoscopize 2D real estate data but also obtain the building property rights model with floor and house and property rights information while ensuring the small model size and low cost. Moreover, this method provides technical support for the 3D management of real estate in China.